METHODS OF ECONOMIC SUBJECTS INTEGRATED TEACHING BY MEANS OF THE ENGLISH LANGUAGE - Світлана Боднар (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2015)
The article discloses the problem of economic subjects integrated teaching by means of the foreign language. The characteristics of the integrated teaching are presented. The peculiarities of the economic subjects integrated teaching by means of the foreign language are highlighted. Professional knowledge and skills that students are to master both in the native and in the foreign languages for professional material application into practice in the foreign language are described. The methods of economic subjects integrated teaching by means of the foreign language, the aim of which is to develop students' ability to implement professional actions that are gradually getting more complicated in a foreign language, have been introduced. The model of stage-by-stage realization of the integrated teaching of two kinds of activity (professional and foreign language) with the description of the interconnected components of the teaching process has been elaborated and presented in the article.